A Comprehensive Review on Piezoelectric Composites for Energy Harvesting and Sensing - Sneha Varshney (International Journal of Electro-Mechanics and Material Behaviour, 2025)
The capacity of piezoelectric composites to transform mechanical energy into electrical energy and vice versa has drawn a lot of interest recently. This property makes them very appealing for use in energy harvesting and sensing applications. These materials combine the high piezoelectric performance of ceramics with the mechanical flexibility and processability of polymers or other matrices, enabling a wide range of practical uses in flexible electronics, wearable systems, and embedded sensor networks. Unlike monolithic ceramics, which are often brittle and difficult to process, piezoelectric composites offer enhanced mechanical robustness and design versatility while maintaining functional efficiency. This review presents a comprehensive analysis of the current landscape of piezoelectric composites, focusing on their material constituents, structural classifications, fabrication techniques, and performance characteristics. It explores various connectivity models such as 0-3, 1-3, and 2-2 composites and evaluates their advantages and limitations in specific applications. The role of nanostructured fillers, eco-friendly alternatives, and multifunctional additives is also discussed in the context of enhancing piezoelectric response and durability. The article further highlights cutting-edge advancements in processing technologies, including 3D printing, electrospinning, and additive manufacturing, which are revolutionizing the development of next-generation piezoelectric devices. Applications in energy harvesting include powering wearable electronics, structural health monitoring, and autonomous wireless sensors, while sensing applications range from biomedical diagnostics to smart infrastructure. Despite rapid progress, challenges such as interface compatibility, material degradation, and scalability remain. This review concludes by outlining potential research directions aimed at overcoming these challenges through novel material design, modeling, and integration strategies. Overall, piezoelectric composites continue to evolve as a key class of materials that bridge the gap between rigid ceramics and soft electronics, paving the way for future innovations in self-powered and intelligent systems.
Keywords: Energy harvesting; Piezoelectric composites; Smart materials; lead-free ceramics; nanocomposites; sensing